2020
DOI: 10.1186/s12889-020-09436-4
|View full text |Cite
|
Sign up to set email alerts
|

Austrian male patients’ gender role conflict is associated with their wish for interpersonal violence to be addressed during patient-physician conversations: a questionnaire study

Abstract: Background: Experiencing interpersonal violence and disclosing this experience to physicians can be associated with fear, shame, denial or emotional turmoil. Expressions of such feelings additionally conflict with masculine gender role ideologies and may be experienced as masculine gender role conflict. Masculine gender role conflict is often associated with men's unwillingness to seek professional help. The current study analyzed the association between masculine gender role conflict and men's wish for patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
(134 reference statements)
0
2
0
Order By: Relevance
“…Similarly, recent reports also suggest that there may be no or even beneficiary relations between individual masculine norms and negative mental health outcomes, such as depression symptoms (Lin et al, 2021;Van Doorn et al, 2021). Concordantly, a recent study from Austria examining 129 men found that stronger GRC experienced due to work-family conflicts was associated with a greater desire to address the topic of interpersonal violence during patient-physician conversations (Komlenac et al, 2020). Such This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Help-seeking Among Menmentioning
confidence: 94%
“…Similarly, recent reports also suggest that there may be no or even beneficiary relations between individual masculine norms and negative mental health outcomes, such as depression symptoms (Lin et al, 2021;Van Doorn et al, 2021). Concordantly, a recent study from Austria examining 129 men found that stronger GRC experienced due to work-family conflicts was associated with a greater desire to address the topic of interpersonal violence during patient-physician conversations (Komlenac et al, 2020). Such This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Help-seeking Among Menmentioning
confidence: 94%
“…Healthcare practitioners may try to use their patients’ CMI to best advantage by reframing the healthcare situations in a way that promotes self-management, empowerment, accountability, and autonomy throughout treatment. In such healthcare settings, patients who strongly conform to masculinity ideologies might be able to utilize healthcare offers after experiencing IPV, whereas at the same time being able to maintain their sense of masculinity ( Komlenac et al, 2020 ; Seidler et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%